2003
DOI: 10.1046/j.1570-7458.2003.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

A second case of genetic host races in Rhagoletis? A population genetic comparison of sympatric host populations in the European cherry fruit fly, Rhagoletis cerasi

Abstract: Despite an increasing acceptance in the biological community for sympatric speciation as a mode of species formation, well documented examples of sympatrically evolved ‘incipient species’ remain rare. The sympatric host races of apple maggot, Rhagoletis pomonella (Walsh), represent one of the most prominent case studies for sympatric speciation via a host shift. The European cherry fruit fly, R. cerasi (L.), shows strong ecological similarities to R. pomonella: (1) infestation of two different host plants, Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…As is well established for some phytophagous insects, such host plant shifts can lead to ecological segregation of populations with appearance of host races and genetic diff erentiation. Th is is well known with R. pomonella (Feder et al 1988;McPheron et al 1988), R. cerasi (L. 1758) ( Diptera: Tephritidae) (Schwartz et al 2003), the European corn borer Ostrinia nubilalis (Hübner 1796) (Lepidoptera: Pyralidae) (Th omas et al 2003), Spodoptera frugiperda (Smith & Abbott 1797) (Lepidoptera: Noctuidae) (Pashley Prowell et al 2004), C. serratus (Sembène 2000) and the pea aphid A. pisum Caillaud & Via 2000). Genetic diff erentiation of such host races can occur within a limited period of time.…”
Section: Evolution Of Host Plant Specialization In Busseola Fuscamentioning
confidence: 99%
“…As is well established for some phytophagous insects, such host plant shifts can lead to ecological segregation of populations with appearance of host races and genetic diff erentiation. Th is is well known with R. pomonella (Feder et al 1988;McPheron et al 1988), R. cerasi (L. 1758) ( Diptera: Tephritidae) (Schwartz et al 2003), the European corn borer Ostrinia nubilalis (Hübner 1796) (Lepidoptera: Pyralidae) (Th omas et al 2003), Spodoptera frugiperda (Smith & Abbott 1797) (Lepidoptera: Noctuidae) (Pashley Prowell et al 2004), C. serratus (Sembène 2000) and the pea aphid A. pisum Caillaud & Via 2000). Genetic diff erentiation of such host races can occur within a limited period of time.…”
Section: Evolution Of Host Plant Specialization In Busseola Fuscamentioning
confidence: 99%
“…Rhagoletis cerasi has a univoltine life cycle and infests cherries, mainly Prunus avium and Prunus cerasus , and honeysuckle, Lonicera xylosteum (Boller & Bush ; Schwarz et al . ). Crossings of males from southern and central European populations with females from northern and eastern European populations showed an egg mortality of 98%, while the reciprocal crosses were fully compatible (Boller et al .…”
Section: Introductionmentioning
confidence: 97%
“…That the highly polymorphic microsatellite loci failed to detect signatures of genetic divergence suggests: (a) that genomic divergence across geography and hosts may be limited to localized regions of the genome not surveyed by the microsatellites, and (b) that gene flow is most likely ongoing and sufficient to homogenise regions of the genome not under geographic selection or divergent selection between sympatric Prunus and Lonicera flies. Schwarz et al (), however, reported R. cerasi host race differences for a single allozyme locus that may be under direct or linked selection, as reported for a number of allozyme loci in R. pomonella (Feder, Chilcote, & Bush, ; Feder et al, ).…”
Section: Discussionmentioning
confidence: 94%